Research on the Reuse of Discharged Soil from EBP Shield Tunnels in Synchronous Grouting Material - Guijun Luo; Chao Xiao; Yuan Liu; Kejun Feng; Qingguo Ren (Advances in Civil Engineering)
Great practical significance and engineering application value can be achieved when the large amount of discharged soil produced by EPB shield tunnels is recycled and comprehensively utilized. As one of the key processes of shield construction, synchronous grouting needs a large amount of bentonite, cement, fly ash, sand, and other materials. The research on the reuse of shield muck as synchronous grouting material is carried out based on Zhengzhou subway project. The physical properties and phase of the discharged soil from EPB shield tunnels are studied by using laboratory tests and XRD. The statistics show that the shield muck meets the performance requirements of bentonite and fine sand in synchronous grouting materials. The optimal grout ratio of the reused muck is obtained based on the optimization idea of multiobjective programming by MATLAB. Considering the combined effect of seepage field, stress field, and the timeliness of the grout, the influences of grouting pressure and the filling rate of synchronous grouting on surface settlement, plastic zone of strata, and segment deformation are analyzed by using finite difference method. The results prove that the surface settlement and segment deformation can be better controlled when the grouting pressure is at 0.18 MPa and the grouting rate is at 120%–150%.